Quality of life in diabetic individuals undergoing renal replacement therapy: systematic review (Research, Society and Development, 2021)
Introduction: Diabetes mellitus is a chronic condition that can lead to health complications. Among the complications, there is diabetic nephropathy, which requires treatment, such as renal replacement therapy, which requires routine modification and can influence quality of life. Therefore, the objective of this review is to analyze the current panorama of the national and international literature regarding the quality of life of individuals with diabetes mellitus undergoing renal replacement therapy. Methodology: The review protocol is registered in the PROSPERO database, the PECO strategy was used, and the guidelines outlined by PRISMA were followed. Searches for articles were performed in the Pubmed, Medline, LILACS, Scielo, IBECS, BRISA, BDENF and CUMED databases until February 2021 and available in all languages. Selected articles were descriptively analyzed and evaluated for methodological quality. Results: The present study consisted of 20 studies, most of which were of moderate methodological quality. Low quality of life prevailed in the summaries of physical and mental components, and aspects of quality of life related to kidney disease were high in most studies. Conclusion: It is concluded that the quality of life of individuals with diabetes mellitus undergoing renal replacement therapy varies according to the context, although it is clear that there is a predominance of low scores in the physical and mental health domains and high scores in the aspects of quality of life related to kidney disease.